2021
DOI: 10.3389/fmicb.2021.735000
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial Transformation of Aromatic Monomers in Softwood Black Liquor

Abstract: The valorization of lignin, a major component of plant-derived biomass, is essential to sustainable biorefining. We identified the major monoaromatic compounds present in black liquor, a lignin-rich stream generated in the kraft pulping process, and investigated their bacterial transformation. Among tested solvents, acetone extracted the greatest amount of monoaromatic compounds from softwood black liquor, with guaiacol, vanillin, and acetovanillone, in an approximately 4:3:2 ratio, constituting ~90% of the to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 42 publications
(75 reference statements)
0
16
0
Order By: Relevance
“…XccA (CT), XccC (BC), and XccB (BCCP) have 55%, 63%, and 45% amino acid sequence identity with SLG_06500, SLG_06510, and SLG_06520, respectively (Table S2). Furthermore, SLG_06500, SLG_06510, and SLG_06520 exhibited 42%, 51%, and 38% amino acid sequence identity, respectively, with apkA (CT), apkB (BC), and apkC (BCCP), the recently predicted AV catabolic enzyme genes in R. rhodochrous GD02 (Table S2) (20). SLG_06490 showed 23% amino acid sequence identity with NagD, a ribonucleotide monophosphatase of E. coli K-12, belonging to the haloacid dehydrogenase (HAD) superfamily (Table S2) (56).…”
Section: Resultsmentioning
confidence: 95%
See 4 more Smart Citations
“…XccA (CT), XccC (BC), and XccB (BCCP) have 55%, 63%, and 45% amino acid sequence identity with SLG_06500, SLG_06510, and SLG_06520, respectively (Table S2). Furthermore, SLG_06500, SLG_06510, and SLG_06520 exhibited 42%, 51%, and 38% amino acid sequence identity, respectively, with apkA (CT), apkB (BC), and apkC (BCCP), the recently predicted AV catabolic enzyme genes in R. rhodochrous GD02 (Table S2) (20). SLG_06490 showed 23% amino acid sequence identity with NagD, a ribonucleotide monophosphatase of E. coli K-12, belonging to the haloacid dehydrogenase (HAD) superfamily (Table S2) (56).…”
Section: Resultsmentioning
confidence: 95%
“…AV and AS are major lignin-derived aromatic monomers produced in alkaline oxidative depolymerization (1316) and base-catalyzed depolymerization of lignin (17-19, 62-68). They are also contained in the black liquor produced during the kraft pulping process (20). This study identified acvABCDEF that encodes AV and AS carboxylase components and showed that these genes help produce value-added chemicals from AV.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations